Editorial - Diaz Dumont, Jorge Rafael (2024)
The National Autonomous University of Tayacaja Daniel Hernández Morillo, presents Vol. 5, No 1 (2024) of the Scientific and Technological Research Magazine “Llamkasun”, which is a publication published biannually by UNAT and managed through the Open Journal System. Its objective is to publish articles resulting from completed research that retain a character of originality, usefulness, scientific and technological relevance; that provide new knowledge on theoretical or practical aspects in the specialty of “Civil Engineering, Industrial Processes and Technologies”, according to the indicated standards. Journal Certified with ISO 9001:2015 - PE22/819943899 Certificate (Publication of scientific articles with implemented quality management system processes - SGS). The Llamkasun Scientific and Technological Research Journal certifies the quality in the publication of original scientific articles, reviewed by blind expert peers and with a very strict similarity system that guarantees the originality of each article for publication. Additionally, the layout and design process of each scientific article was also certified. We would like to thank all the authors – national and foreign researchers who entrusted their research to the Scientific and Technological Research Journal “Llamkasun” – who were impartially evaluated in a process called “blind peer evaluation system” for their participation. members of the editorial board, to the teachers and students of this university and in general to the entire UNAT university community.